Effects of Irrigation on N2O Emissions in a Maize Crop Grown on Different Soil Types in Two Contrasting Seasons - Lucia Ottaiano; Ida Di Mola; Paul Di Tommasi; Mauro Mori; Vincenzo Magliulo; Luca Vitale (Agriculture, 2020)
Crop management and soil properties affect greenhouse gas (GHG) emissions from cropping systems. Irrigation is one of the agronomical management practices that deeply affects soil nitrous oxide (N2O) emissions. Careful management of irrigation, also concerning to soil type, might mitigate the emissions of this powerful GHG from agricultural soils. In the Mediterranean area, despite the relevance of the agricultural sector to the overall economy and sustainable development, the topic of N2O emissions does not have the same importance as N2O fluxes in temperate agricultural areas. Only some research has discussed N2O emissions from Mediterranean cropping systems. Therefore, in this study, N2O emissions from different soil types (sandy-loam and clay soils) were analyzed in relation to the irrigation of a maize crop grown in two contrasting seasons (2009–2010). The irrigation was done using a center pivot irrigation system about twice a week. The N2O emissions were monitored throughout the two-years of maize crop growth. The emissions were measured with the accumulation technique using eight static chambers (four chambers per site). Nitrogen fertilizer was applied in the form of ammonium sulphate and urea with 3,4 dimethylpyrazole phosphate (DMPP) nitrification inhibitors. In 2009, the N2O emissions and crop biomass measured in both soil types were lower than those measured in 2010. This situation was a lower amount of water and nitrogen (N) available to the crop. In 2010, the N2O fluxes were higher in the clay site than those in the sandy-loam site after the first fertilization, whereas an opposite trend was found after the second fertilization. The soil temperature, N content, and soil humidity were the main drivers for N2O emission during 2009, whereas during 2010, only the N content and soil humidity affected the nitrous oxide emissions. The research has demonstrated that crop water management deeply affects soil N2O emissions, acting differently for denitrification and nitrification. The soil properties affect N2O emission by influencing the microclimate conditions in the root zone, conditioning the N2O production.